Assessing the Meritocratic and Equitable Nature of Higher Education in Bangladesh: Identifying Barriers and Proposing Strategies for Improvement - Mina, Ibrahim (My University, 2023)
Equity and meritocracy in higher education are universally recognized goals, yet the attainment of these objectives is often impeded by multifaceted barriers. In the context of Bangladesh, this study employed a quantitative methodology to systematically analyze the obstacles, targeting students' perceptions at three educational stages: pre-university students, university students, and university graduates. Utilizing a comprehensive questionnaire, the research scrutinized perceptions related to fairness, transparency, barriers, awareness, and the impacts on equity and meritocracy. A complex landscape was revealed, wherein gender discrimination was not a significant barrier, contrary to initial expectations. Instead, pervasive hindrances emerged such as limited access to resources, socioeconomic discrimination, quotas, corruption, and political influence. The findings illustrate significant predictors that influence perceived equity and meritocracy, including Barriers to Equity and Meritocracy (BEM), Awareness (AWN), and Impact of Barriers (IOB), exhibiting variations across the educational journey. Moreover, the analysis underscores the evolution of specific factors like Perceptions of Fairness and Transparency (PFT) as students progress through their education. Contributing nuanced insights, this study enhances the understanding of the complexities surrounding equity and meritocracy within Bangladesh's higher education system. The results emphasize the necessity of context-specific interventions and policies, tailored to address the identified barriers at various educational levels. Practical implications include actionable strategies for policymakers and educators to foster a merit-based system, resonating with the unique challenges identified within the Bangladeshi context. In conclusion, this research provides a robust analysis of the multifaceted challenges in achieving equity and meritocracy in higher education in Bangladesh, delineating key predictors and offering targeted solutions. The study represents a crucial advancement towards a more equitable educational landscape in Bangladesh, with implications that may extend to similar global contexts. By spotlighting these significant challenges and proposing tailored interventions, this research lays a foundational groundwork for future investigations, aiming at refining practices and policies for universal access and opportunity within higher education.
Keywords: Barriers, Challenges, Equity and Meritocracy, Awareness, Perceived Fairness and Transparency, Quantitative Method, Higher Education System, Bangladesh